Fizjologiczne podstawy badania ostrości wzroku - Figurska, Małgorzata; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The paper presents information about types of acuity tasks, visual acuity limitations and contrast sensitivity function. Measurements of resolution acuity may be interpreted as estimates of spatial density of the mosaic of photoreceptors and ganglion cells of the living human eye. Physiological basis such as Raleigh's criteria, sampling theory and filtering theory of visual resolution are described.